Model Kognitif Sosial Bandura dalam Edukasi Menyusui: Literature Review - Wahyuni, Nyimas Sri; Rustina, Yeni (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Providing breastfeeding education to mothers requires effective methods to achieve maternal skills inbreastfeeding. One method of learning uses video by applying Bandura's Social Cognitive model. Searchliterature through the Scopus, Ebsco, Science direct and Proquest web sites with keywords: mother, video,breastfeeding. The purpose of this literature study is to determine the effectiveness of breastfeedingeducation using video and discuss its application with the Social Bandura Cognitive model approach tonursing practice. This review identifies twenty articles to be criticized; article inclusion criteria publishedfrom 2015 to 2020; experimental research; video intervention; the focus of research results is theknowledge and ability of breastfeeding mothers; and written in English. Breastfeeding education usingvideos becomes persuasive for mothers and effective interventions. This learning method involvesinteraction between mothers and nurses, so nurses can help them analyze the videos they receive and canprovide stronger and more directed support for nursing mothers.